2002
DOI: 10.1038/sj.bjc.6600071
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 (p9Ka) protein in colon carcinoma and liver metastases: association with carcinoma cells and T-lymphocytes

Abstract: The presence of the EF-hand-calcium-binding protein S100A4 in the carcinoma cells of the primary tumour is associated with a shorter survival time of a group of breast cancer patients. In colon cancer, primary tumours as well as metastases to the liver can be studied. Here we show, using quantitative PCR applied to RNA from 24 normal colon, four liver tissues, 24 colon carcinoma specimens, and 24 livers containing colonic carcinoma metastases, that the level of S100A4 mRNA was significantly higher in the carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 12 publications
2
59
2
3
Order By: Relevance
“…This finding is confirmed by former studies analyzing S100A4 mRNA levels in solid tissues of colon cancer patients. 29,45 We and others determined an independence of S100A4 mRNA expression determined in colon tumor tissues of stages I, II, and III.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding is confirmed by former studies analyzing S100A4 mRNA levels in solid tissues of colon cancer patients. 29,45 We and others determined an independence of S100A4 mRNA expression determined in colon tumor tissues of stages I, II, and III.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was also revealed by earlier studies performed with colon cancer tissues. 29,45 In addition, S100A4 mRNA expression is of prognostic value for the development of metachronous distant metastases when determined in tissues of the nonmetastasized primary tumor. 29 However, only three of all newly diagnosed 64 nonmetastasized primary tumors, with blood samples taken at the day of the first diagnosis, have so far developed distant metastases metachronously.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From dendritic cells, they have many similarities with respect to their effect on T cells. We found 2 genes previously implicated in liver homing, Cxcr6 49 and S100a4, 52 to be induced by liver-derived dendritic cells. Surprisingly, many granzymes were also up-regulated in the liver compared with spleen.…”
Section: Dendritic Cells Imprint Allogeneic T Cells 2935mentioning
confidence: 92%
“…In CRC, S100A4 is overexpressed compared to normal mucosa and adenomas, and higher expression has been observed in liver metastases than in primary tumors 4, 5. Several studies have shown that S100A4 is a strong predictor of poor survival in patients undergoing curatively intended surgery 6, 7, 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%